Grammatical consistency in the Qur’anic text, Surat Ad-Duha as a model - Bashar Mayouf Taama, Dr. (lark, 2025)
The study aimed to uncover the aspects of grammatical cohesion, a linguistic mechanism through which textuality is achieved, in the text of Surah Ad-Duha by analyzing its structure and describing the system it comprises. It further aimed to highlight the cohesion mechanisms on which the text relied, namely (reference, ellipsis, and conjunction), which together form the linguistic fabric of relationships between both internal and external structures. The study revealed that cohesion in the text is established through linguistic features that contribute to its unity and the organization of its components. For instance, reference is considered one of the elements of textuality that enhances linguistic cohesion by playing a prominent role in linking parts of the text and making it coherent. This was observed in both main and subsidiary chains, alongside ellipsis and conjunction. These elements formed the focus of the study in terms of analysis and application.
Keywords: consistency, grammatical consistency, text, Surat Al-Dhuha.